CURRENT DEVELOPMENT TRENDS IN UZBEKISTAN'S FOREIGN TRADE - Kamolov Uygun Tulkinovich (American Journals, 2025)
Uzbekistan's foreign trade has undergone significant transformations in recent years, influenced by economic reforms, international trade agreements, and geopolitical factors. This paper analyzes the current development of Uzbekistan’s foreign trade, highlighting trends in exports and imports, trade balance dynamics, and key trading partners. The study employs statistical data and policy analysis to assess the impact of government measures on trade liberalization and economic diversification. Additionally, challenges such as tariff barriers, logistics, and global economic fluctuations are discussed. The findings suggest that while Uzbekistan has made considerable progress in expanding its foreign trade, further structural improvements are required to enhance global competitiveness.
Keywords: Uzbekistan, foreign trade, trade balance, economic development, international trade, export, import, trade policy.